Gauging two sides of regional economic resilience in Western Germany: Why resistance and recovery should not be lumped together - Franziska Pudelko; Christian Hundt (Philipps-University Marburg, Department of Geography, 2017)
The paper empirically investigates the economic resilience of Western German regions in the wake of the Great Recession of 2008/2009. In particular, the focus is laid on the influence of regional agglomeration economies (arising from specialization, related and unrelated variety) and the explicit subdivision of shortterm resilience into resistance and recovery. The necessity to distinguish between different factors and phases is well documented by means of the OLS regression results as all three types of agglomeration economies reveal varying, if not opposing directions of influences across the resistance and recovery phase. A pregnant example refers to regional specialization. Not only does it show a negative impact on resistance while exerting a positive influence during the recovery phase, but it is also mediated by the regional share in manufacturing workforce. This workforce reveals opposing phase-specific effects itself. Hence, ignoring the two-component structure of short-term resilience entails the risk of imprecise, if not false conclusions on the driving mechanisms stabilizing and/or destabilizing regional economies in times of crisis.
Keywords: R11; R12; E32; 330; regional economic resilience; resistance; recovery; agglomeration economies; industry structure